1997
DOI: 10.1002/(sici)1097-461x(1997)65:5<565::aid-qua21>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-relativistic LCGTO DFT calculations for atoms using the Douglas-Kroll transformation

Abstract: ABSTRACT:Haberlen and Rosch HR demonstrated Chem. Phys. Lett. 199, 491Ž.x Ž . 1992 the feasibility of performing scalar-relativistic, density functional theory DFT Ž . linear combination of Gaussian-type orbitals᎐fitting function LCGTO-FF calculations on clusters of atoms using an ''incomplete'' Douglas᎐Kroll transformation. Some of the approximations used in their multiatom calculations have not yet been fully explored for isolated atoms, especially the neglect of matrix elements involving vector products of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The separation into SO and SR terms is clear for E 1 ½m eff , but not for E 2 ½m eff [17]. The first-order SO operator in E 1 ½m eff is…”
Section: Methodsmentioning
confidence: 99%
“…The separation into SO and SR terms is clear for E 1 ½m eff , but not for E 2 ½m eff [17]. The first-order SO operator in E 1 ½m eff is…”
Section: Methodsmentioning
confidence: 99%
“…So far, the scalar relativistic method has been implemented in several methods: the augmented-plane-wave (APW) method, 3) the linearized muffin-tin-orbital (LMTO) method, 4) the Korringa-Kohn-Rostoker (KKR) method, 5) and the linear-combination-of-atomic-orbitals (LCAO) method. [6][7][8][9][10][11][12][13][14][15][16][17][18] In particular, the usefulness of the scalar relativistic formulation given by Koelling and Harmon 19) for the APW, LMTO, and KKR method has been established in the last two decades. On the contrary, there are no standard scalar relativistic formulations for the LCAO method; it is difficult to apply directly the Koelling-Harmon formulation to the LCAO method because this method uses fixed basis sets in contrast to the APW, LMTO, and KKR methods.…”
Section: §1 Introductionmentioning
confidence: 86%
“…Although this approach encountered a difficulty due to singular behavior of the resultant terms near nuclei, the frozen core approximation has circumvented this difficulty. 11) Another approach [13][14][15][16][17] is to use Douglas-Kroll-Hess (DKH) transformation, [20][21][22] which generates no singular terms in contrast to the case of the FWT transformation. Also, there is an alternative approach which uses pseudopotential for simulating the scalar relativistic effects.…”
Section: §1 Introductionmentioning
confidence: 99%
“…Throughout the remainder of this work, it will be assumed that all of the spin-orbit coupling terms in equation ( 3) are neglected to obtain the scalar-relativistic EFP approximation. (A detailed discussion of the separation of the relativistic corrections into scalar-relativistic and spin-orbit coupling terms has been presented elsewhere [23] and will not be repeated here.) Analytical evaluation of the GTO matrix elements for the momentum-space operators in equation ( 3) has not proven to be practical thus far.…”
Section: The Scalar-relativistic Lcgto Methodsmentioning
confidence: 99%
“…Häberlen and Rösch [5] achieve a further reduction in the resources required for their calculations by dropping all terms in the nuclear-only EFP equation that require p × v n p; this is the HR approximation. A recent series of test calculations on isolated atoms [23] found that the HR approximation produces one-electron eigenvalues for the chemically active valence states that differ little from those obtained with the complete scalar-relativistic Douglas-Kroll-Hess transformation. This then is the version of scalar relativity implemented in GTOFF.…”
Section: The Scalar-relativistic Lcgto Methodsmentioning
confidence: 99%